tawassu’ al-’imbarāṭūriyah al-’āšūriyyah fī manṭiqatay al-Ḫābūr wa-’l-Furāt al-’ausaṭ: naẓarah ǧadīdah - Līfarānī, Māryū
Mario Liverani; Assyrian Imperial Expansion in the Habur and Middle Euphrates Regions: a New View; ersch. 1986?; in Arabic, translated and abridged by Šauq? Ša'?.